THE ANALYSIS FACTOR IN CORRELATION TO EXCLUSIVE BREASTFEEDING IN JURISDICTION OF BALEN - HIDAYAH, WAQIDIL; LUTHFIA, ERIEN (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2016)
ABSTRACTMother?s milk is best food for baby and can?t be replaced. Exclusive breastfeeding was gived mother?s milk without other side dish at the age of 0-6 months and continued 2 year with other side dish ( Maryunani, 2012). The data of Puskesmas Balen baby with exclusive breastfeeding only 4,00%, the percentage of baby with breastfeeding 0-6 months in Bojonegoro City 2012 only 12,5%. While giving coverage of exclusive breastdfeeding is 80% ( Indonesia Health Profile, 2012). Anticipated between factor in correlation to exclusive breastfeeding is knowledge factor, attitudes and occupation factor. The general objective of this research to know correlation and dominant factor of exclusive breastfeeding in jurisdiction of Puskesmas Balen.The design of the research was an analytical survey with cross sectional approach. The applies method is accidental sampling with number of samples 87 mothers. The data was collected is primary data and instrument of research used questionaire. The processing of the data was used univariate analysis ( frequency distribution), bivariate analysis ( chi square), and multivariate analysis ( double logistics regression).The Result of research shows the factor relation to exclusive breasfeeding is knowledge with p value = 0,001, attitude p value = 0,005, and factor that did?t correlated is occupation with p value = 0,053 with value alpha 5% (? = 0,5%), and the dominance factor is attitude of mother?s have the power of relation with OR = 3,351. Inferential that attitude is dominant factor in exclusive breastfeeding.Suggested to the Department of Health Bojonegoro City to make policy for all Puskesmas in Balen to give more complete information can be change of opinion sight about exclusive breastfeeding and changes position of mother to support gives exclusive breastfeeding for baby and  the target of coverage ASI Eksklusif can be reached. Keyword                      : knowledge, attitudes, work, the  exclusive breasfeeding